THE DEVELOPMENT OF THE CREATIVE ECONOMY IN INDONESIA BEFORE AND DURING THE COVID-19 PANDEMIC: A COMPARATIVE ANALYSIS (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The creative economy has become one of the driving sectors of economic growth. The development of the creative economy sector has been disrupted during the COVID-19 pandemic. The COVID-19 pandemic has had a major influence on the development of economic sectors, including the creative economy sector. The government needs to pay greater attention to the creative economy sector so that it continues to advance after the COVID-19 pandemic. This paper aims to conduct a comparative test of the development of the creative economy before and during the COVID-19 pandemic. This type of research uses comparative analysis to determine the comparison of an indicator of the development of the creative economy sector before and during the COVID-19 pandemic. The data analysis method used is a comparative statistical test. The results showed that in general there was no significant difference in the development of the creative economy in Indonesia between before and during the Covid-19 pandemic.
Keywords: Creative Economy; Comparative Test; Pandemic